Analisis Beta terhadap Return Saham dalam Indeks LQ 45 - Anwar Anwar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the world of investment, there is a strong correlation between risk and return. An investor must be aware of the risks that arise and the expected rate of return. The rate represents the risk of betting on a particular stock; if the rate for the stock is marginal, it also represents the risk for the stock. The purpose of the reverse listing is to determine the effect of Stock Prices on Stock Returns. Reverse listing is a type of associative listing that uses a quantitative approach. The data used in the reverse listing is the latest stock price obtained from the official website of the Indonesian Stock Exchange (IDX). The population in the reverse listing is all companies listed on the LQ 45 Index from January 2022 to December 2022, totaling around 83 companies. The sample of the initial release is based on the criteria that have been set and used by approximately 10 companies. The initial release was carried out on all companies listed in the LQ 45 Index from January 2022 to December 2022, totaling approximately 83 companies. The initial release sample is based on the criteria that have been set and used by approximately 10 companies.